The Influence of The Agricultural Sector and Trade Sector on The Gross Regional Domestic Product Growth Rate in West Sulawesi in 2017-2023 - Fadli Ahmad Aaenal Lipsa, Muh; Heryati, Yati; Rahman, Ratna (Golden Ratio of Social Science and Education, 2024)
This study aims to evaluate the significant impact of the agricultural and trade sectors on the growth rate of Gross Regional Domestic Product (GRDP) in West Sulawesi from 2017 to 2023. The analysis was conducted using GRDP data at constant prices, which reflects the contribution of each sector to the overall GRDP. Data collection techniques included observation and secondary data retrieval from the BPS website. The data were processed and analyzed using multiple linear regression. The regression analysis results indicate that the agricultural sector has a t-coefficient of 11,665.550 with a significance value of 0.000, while the trade sector has a t-coefficient of 10,678.826 with a significance value of 0.000. These findings confirm that both sectors significantly influence the GRDP growth rate. The F-test results further validate this relationship, showing that the agricultural sector (F-value = 136,085,062.042) and the trade sector (F-value = 114,037,315.965) significantly explain variations in GRDP. Throughout the study period, the agricultural sector's contribution to GRDP remained stable at around 39%, while the trade sector accounted for approximately 10%. However, a decline in contribution observed in 2024 suggests fluctuations that warrant further analysis. These findings highlight the critical role of both sectors in driving economic growth in West Sulawesi.